Postoperative small bowel obstruction secondary to single malformed staple following laparoscopic total abdominal colectomy. Issue 10 (24th October 2020) - DiChiacchio, Laura; O'Neill, Natalie A; Kligman, Mark; Bafford, Andrea C
Abstract: Surgical staplers are ubiquitous in gastrointestinal surgery, especially laparoscopy. Intraperitoneal staples are designed to be inert and are generally regarded as benign; however, complications from primarily malformed staples can rarely occur. Here, we present a case of early mechanical postoperative small bowel obstruction due to a surgical staple following laparoscopic total abdominal colectomy and end ileostomy creation performed for medically refractory ulcerative colitis. Management consisted of diagnostic laparoscopy and careful extraction of a malformed surgical staple tethering a loop of small bowel to the rectal stump. Eight similar cases following gastrointestinal surgery have been identified in the literature, all occurring in the first 2 weeks following laparoscopic appendectomy. To our knowledge, this is the first case described following laparoscopic total abdominal colectomy, with high-grade small bowel obstruction at the level of the rectal stump staple line.